Transcriptomic analysis of Malaysian rice seedlings (Oryza sativa L. ssp. indica) in early responses to salt-shock - Mohamad Juri, Nor Mustaiqazah (2017)
Salinization of rice cultivation land is progressively enlarged thus negatively impair the world‘s rice bowl. Due to the polygenic nature and complexity of salinity tolerance mechanisms in plants, the development of new rice varieties with better adaptation to salinity has become a great challenge. Regarding this, transcriptomic profiling was seen as a promiseable technology for a holistic understanding of salinity tolerance mechanisms in rice. Here, by using Illumina HiSeq 2000 sequencing platform, transcriptomes of salt-tolerant Malaysian rice variety MR211 and salt-sensitive MR220 were analyzed after nine hours of severe salinity stress (12 dS/m) treatment, labeled as S211 and S220, respectively. After trimming, a total of 76,456,236 (S211) and 57,323,996 (S220) high-quality reads were obtained. The assembly of these reads resulting a total of 20,853 (S211) and 19,315 (S220) genes. Through comparative expression between both samples, 252 significant genes were differentially expressed and were dominated by variety-induced genes (n=235; 93.3%) with majority of them (n=221; 88%) were categorized as uniquely expressed in salt-tolerant MR211. Further pathway based analysis on the DEGs that were categorized as ―uniquely‖ and ―higher expressed‖ in S211 when compared to S220 had assigned them to 33 KEGG pathways with the highest number of DEGs were accounted in purine metabolism and thiamine metabolism pathways. The functional annotation of these group of DEGs also revealed the presence of regulatory genes such as transcription factors (TFs), protein kinases and protein phosphatases, as well as functional genes that involves in various adaptation mechanisms such as mechanical support, ROS-scavenging system, ion exclusion and intracellular compartmentalization thus suggest how this salt tolerant genotype (MR211) gains its salt adaptation trait. The expression accuracy and reproducibility of the 252 DEGs identified from the RNA-seq experiment were further verified through RT-PCR followed by qRT-PCR analysis. Nine genes were selected as the representative with 4 of them namely FER2, Thaumatin, VI and UBC were in line with data generated from the RNA-seq analysis. The other 2 (MT and HOX16) showed a contradict trend of expression as compared to the RNA-seq data, whereas the other three candidate genes (PSII, SAPK6 and PAO) had exhibited a similar (no difference) level of expressions between S211 and S220. Next, the incorporation of control (untreated) cDNA samples (C211 and C220) in the expression analyses had revealed the expression of the genes in untreated plants as compared to after being subjected to salt stress. The expression analyses had highlighted UBC and SPK6 genes as the most responsive towards salinity stress in MR211 and MR220, respectively thus might represent their uniqueness in response to salinity stress.